Chemical characterization of imperata cylindrical (`Lalang`) and pennisetum purpureum (Napier grass) for bioethanol production in Malaysia - Liong, Yan Yee; Halis, Rasmina; Mohamed, Rozi (Universiti Putra Malaysia Press, 2013)
Grass is a candidate biomass producer because it is fibrous and it thrives well on poor soils. The chemical properties of two grass species growing naturally and abundantly on idle lands in Malaysia were investigated in this study. The grasses selected were Imperata cylindrical (`Lalang`) and Pennisetum purpureum (Napier grass). For the purpose of analysis, Napier grass was further divided into male and female plants, and stem and leaves. Lignin, hemicellulose and cellulose contents were determined using the TAPPI standard methods. `Lalang` was found not to be an attractive biomass producer because of its high lignin content (22%) (P<0.05). On the contrary, Napier grass, particularly the female stem, had low lignin content (13%) (P<0.05) and a favourably high level of cellulose (46%) (P<0.05). In the female leaf, lignin content was higher (20.7%), while the cellulose content (30.4%) was lower compared to the stem. Although the cellulose content in the male stem (51%) was slightly higher (P<0.05) than the female, its lignin was two-fold above that of the female stem, making it a less desirable biomass producer. Hence, it was concluded that female Napier grass has a good potential of becoming a biomass producer in bioethanol production in Malaysia.